2007
DOI: 10.1002/ptr.2021
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids and flavonoids from the fruits of Vitex agnus‐castus and antioxidant activity of the fruit extracts and their constituents

Abstract: From the n-hexane fraction of the fruits of Vitex agnus-castus, two labdane-type diterpenes, vitetrifolin B and C, were isolated by means of multiple chromatographic separations, together with the previously identified rotundifuran, vitexilactone and the sesquiterpene spathulenol. From the EtOAc fraction, eupatorin was identified for the first time, besides the known casticin, penduletin, vitexin and orientin. The n-hexane, EtOAc and MeOH-H(2)O fractions of the MeOH extract of Agni-casti fructus were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 17 publications
4
38
0
6
Order By: Relevance
“…Further, in the 13 C-NMR spectra of 1 obtained by measurements using CDCl 3 , C 5 D 5 N, and CD 3 OD as solvents, the peak height of 11 signals, which were assigned to C-2-C-7, C-9, C-11, C-12, C-19, and C-20, was found to be fairly low and a signal due to C-1 could not be detected (Table 2). A similar phenomenon, which was ascribable to short spin-spin relaxation times, was reported in the case of the 13 C-NMR signals for sclareol (9 C-NMR spectra of 2 were similar to those of 1, except for the absence of signals due to one olefinic proton and one olefinic methine carbon, and the presence of a signal due to one olefinic quaternary carbon. In a manner similar to that in the case of 1, these 1 H-and 13 C-NMR signals were examined in detail, and the planar structure of 2 was determined, as shown in Fig.…”
Section: Notessupporting
confidence: 79%
See 1 more Smart Citation
“…Further, in the 13 C-NMR spectra of 1 obtained by measurements using CDCl 3 , C 5 D 5 N, and CD 3 OD as solvents, the peak height of 11 signals, which were assigned to C-2-C-7, C-9, C-11, C-12, C-19, and C-20, was found to be fairly low and a signal due to C-1 could not be detected (Table 2). A similar phenomenon, which was ascribable to short spin-spin relaxation times, was reported in the case of the 13 C-NMR signals for sclareol (9 C-NMR spectra of 2 were similar to those of 1, except for the absence of signals due to one olefinic proton and one olefinic methine carbon, and the presence of a signal due to one olefinic quaternary carbon. In a manner similar to that in the case of 1, these 1 H-and 13 C-NMR signals were examined in detail, and the planar structure of 2 was determined, as shown in Fig.…”
Section: Notessupporting
confidence: 79%
“…1) This fruit has been reported to contain essential oils, iridoids, flavonoids, and diterpenoids. [1][2][3][4][5][6][7][8][9] Further, linoleic acid isolated from this fruit was identified as an estrogenic compound. 10) In the course of our study on the constituents of Verbenaceae plants, [11][12][13][14] we have investigated the constituents of the fruit of V. agnus-castus.…”
Section: Notesmentioning
confidence: 86%
“…1) This fruit has been reported to contain essential oils, iridoids, flavonoids, and diterpenoids. [1][2][3][4][5][6][7][8][9] Further, linoleic acid isolated from this fruit was identified as an estrogenic compound. 10) In a previous paper, 11) we reported the isolation and structural elucidation of seven diterpenoids from the hexane extract of V. agnuscastus.…”
mentioning
confidence: 86%
“…Anti-inflammatory and anti-oxidative effects have been previously reported for VAC extracts and several single VAC constituents [25,52,53]. For example, Choudary et al demonstrated LO enzyme-inhibiting activity of casticin in vitro [54], and the flavonoid vitexin inhibited proinflammatory cytokine production and inflammationinduced pain [23] in an in vivo experimental inflammation model.…”
Section: Reduction Of Pro-inflammatory Signaling Molecules By Bno 1095mentioning
confidence: 98%
“…The mechanism of action of VAC herbal extracts in treating menstrual symptoms has not been completely elucidated, perhaps due to the large number of potentially active extract constituents, including iridoids, flavonoids, and diterpenes [22][23][24][25][26]. For example, a large body of evidence suggests that VAC extracts acts in the brain at dopamine D 2 receptors of the hypothalamus/ pituitary gland axis to inhibit the systemic release of prolactin from the pituitary gland resulting in the relief of PMS symptoms [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%